'Kindness isn't important, we need to be scared': disruptions to the praxis of peace education in an Indian school. Issue 2 (3rd May 2020) - Kurian, Nomisha
ABSTRACT: There is a dearth of research on the frustrations, moral dilemmas and challenges non-Western teachers might face in the everyday praxis of peace education. To address this gap, this study analyses how violence is negotiated and understood in an Indian school seeking to build a culture of peace. Interviews with eight teachers and four students are analysed using grounded theory. Firstly, the study discusses a teacher's response to a student witnessing domestic violence. Thereby, it explores the limits of peace education in the face of home-school boundaries and societal stigmas. Secondly, the study discusses a teacher's attempt to help an abused child labourer. It questions the extent to which peace education can tackle systemic inequalities and the danger of the field reproducing exclusionary structures. Thirdly, the study discusses the intergenerational politics of children endorsing corporal punishment. It seeks to demonstrate how socio-economic pressures and historical legacies might lead to children legitimating violence against their own bodies. By exploring the fractures and gaps within peace education in an understudied non-Western context, the study aims to raise larger questions about the structures and norms hindering ideals of peace and the need for peace education to prioritise criticality, context and reflexivity.